تنفيذ حكم التحكيم التجاري الدولي في الجزائر - بزيط حورية (جامعة محمد بوضياف المسيلة, 2019)
لتنفيذ حكم التحكيم التجاري الدولي في الجزائر يقتضي هذا الاجراء أن يمر بعدة مراحل أولها الاعتراف بهذا الحكم متى كان موجود وغير مخالف للنظام العام الدولي. وتلي هذه المرحلة وبنفس الشروط يصدر رئيس المحكمة التي أصدرت أحكام التحكيم في دائرة اختصاصها أو محكمة محل التنفيذ ليقوم القاضي ببسط رقابته على حكم التحكيم التجاري الدولي والتأكد من استيفاء الشروط المقررة قانون (المادة 1051 ق إ م إ ج). وبصدور الأمر بالتنفيذ يصبح حكم التحكيم التجاري الدولي سندا تنفيذيا قابلا للتنفيذ بكل الطرق القانونية على جميع أراضي الجمهورية، وهذا ما يفترض تنفيذه من قبل الأطراف بالطريقة الودية إلا أنه يمكن لأحد الأطراف أن يتقاعس عن تنفيذ الحكم مما يجعل الطرف الآخر يلجأ للتنفيذ الجبري سواء أكان تنفيذا مباشرا أو غير مباشر. الكلمات المفتاحية: حكم التحكيم التجاري الدولي، الاعتراف، الأمر بالتنفيذ، الرقابة القضائية، التنفيذ الجبري، التنفيذ المباشر، التنفيذ غير المباشر. Summary: For the implementation of the International commercial arbitration provision in Algeria, this procedure requires that the provision be passed in several stages, the first of which is recognized when it exists and is not contrary to international public order. This is followed by the same conditions as the presiding judge of the court which issued the arbitral awards within its jurisdiction or a court of enforcement, to establish its control over the international commercial arbitration and to ensure that the requirements established by law are met (article 1051). With the order of execution, the International Commercial Arbitration award becomes an enforceable executive bond by all legal means throughout the territory of the Republic, which is supposed to be implemented by the parties in a friendly manner, but one party may fail to implement the provision, which would make the other party resort to enforcement Forced or direct execution. Keywords: International commercial arbitration, recognition, enforcement order, judicial control, forced execution, direct execution, indirect execution.
Keywords: حكم التحكيم التجاري الدولي، الاعتراف، الأمر بالتنفيذ، الرقابة القضائية، التنفيذ الجبري، التنفيذ المباشر، التنفيذ غير المباشر.